(untitled) (Clinics, 2013)
OBJECTIVE: The aim of this study was to evaluate the effect of oral tamoxifen treatment on the number of myofibroblasts present during the healing process after experimental bile duct injury. METHODS: The sample consisted of 16 pigs that were divided into two groups (the control and study groups). Incisions and suturing of the bile ducts were performed in the two groups. Tamoxifen (20 mg/day) was administered only to the study group. The animals were sacrificed after 30 days. Quantification of myofibroblasts in the biliary ducts was made through immunohistochemistry analysis using anti-alpha smooth muscle actin of the smooth muscle antibody. Immunohistochemical quantification was performed using a digital image system. RESULTS: In the animals treated with tamoxifen (20 mg/day), there was a significant reduction in immunostaining for alpha smooth muscle actin compared with the control group (0.1155 vs. 0.2021, p = 0.046). CONCLUSION: Tamoxifen reduced the expression of alpha smooth muscle actin in the healing tissue after bile duct injury, suggesting a decrease in myofibroblasts in the scarred area of the pig biliary tract. These data suggest that tamoxifen could be used in the prevention of biliary tract stenosis after bile duct surgeries.